Comparison study of beach geometrics and beach sand gradation related to abrasion potential based along the West Sumatra Province. (November 2019) - Putra, Y; Hakam, A; Istijono, B; Junaidi,; Adji, B M
Abstract: The West Sumatra beach is very beautiful and has much diversity in terms of their natural properties. This paper elaborating the diversity of the West Sumatra Beach related to their abrasion potential. Field investigation conducted to collect the nature diversities such as the plantation, sands and the geometric. The sand samples have been taken from beaches and brought to the laboratory to investigate their physical properties. The geometric of the beaches were analysed to gain the specific parameter which are comparable each other. The special study on the role of vegetation on abrasion protection as well as numerical modelling of their mechanism also had been studied and reviewed in this study. Those diversities then are turned into the engineering parameter and linked each other to gain their relation to abrasion potential. This study than can redraw the relation between the physical soil properties as well as the beach geometric with the abrasion potential of the beaches. The plantations on the beaches also gave a good correlation to the abrasion problems. The study can give better understanding between the beach abrasion problems with their nature of geology and biology as well as human activities. This study then suggested that to protect the beach abrasion it is necessary to investigate many things including many fields such as engineering, coastal, geology, biology as well as social science.